Do miRNAs Have a Role in Platelet Function Regulation? - Garcia, A.; Dunoyer-Geindre, Sylvie; Fontana, P. (Hämostaseologie, 2021)
MicroRNAs (miRNAs) are a class of non-coding RNAs known to repress mRNA translation and subsequent protein production. miRNAs are predicted to modulate many targets and are involved in regulating various cellular processes. Identifying their role in cell function regulation may allow circulating miRNAs to be used as diagnostic or prognostic markers of various diseases. Increasing numbers of clinical studies have shown associations between circulating miRNA levels and platelet reactivity or the recurrence of cardiovascular events. However, these studies differed regarding population selection, sample types used, miRNA quantification procedures, and platelet function assays. Furthermore, they often lacked functional validation of the miRNA identified in such studies. The latter step is essential to identifying causal relationships and understanding if and how miRNAs regulate platelet function. This review describes recent advances in translational research dedicated to identifying miRNAs' roles in platelet function regulation.
Keywords: microRNA; platelet function; biomarker